2009
DOI: 10.1007/s10336-009-0427-x
|View full text |Cite|
|
Sign up to set email alerts
|

Reduced blood parasite prevalence with age in the Seychelles Warbler: selective mortality or suppression of infection?

Abstract: Avian malaria can affect survival and reproduction of their hosts. Two patterns commonly observed in birds are that females have a higher prevalence of malaria than do males and that prevalence decreases with age. The mechanisms behind these patterns remain unclear. However, most studies on blood parasite infections are based on cross-sectional analyses of prevalence, ignoring malaria related mortality and individual changes in infection. Here, we analyse both within-individual changes in malaria prevalence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 50 publications
5
67
1
Order By: Relevance
“…Our results do not support the findings of several studies showing that young individuals are more infected than adults (Weatherhead and Bennett 1991;Sol et al 2013;van Oers et al 2010).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Our results do not support the findings of several studies showing that young individuals are more infected than adults (Weatherhead and Bennett 1991;Sol et al 2013;van Oers et al 2010).…”
Section: Discussioncontrasting
confidence: 80%
“…However, other studies have also shown a decrease in parasite prevalence over host age (Hudson and Dobson 1997;Sol et al 2003;van Oers et al 2010) or no age effect (Ricklefs et al 2005;Latta and Ricklefs 2010). Because we were not able to resample individuals across time, we are unable to determine if infected juveniles managed to suppress infections later in life or if they died before becoming adults.…”
Section: Discussionmentioning
confidence: 93%
“…Similar results were recorded by Islam et al(2013) in Bangladesh (33.3% and 3.5%), Msoffe et al(2010) in Tanzania (63% and 11%) and El-Magd et al(1988) in Egypt (60.7% and 20.0%) in adult and young birds, respectively. On the contrary, in some studies, higher prevalence was reported in young birds than in adults (Van Oers et al 2010;Hudson and Dobson, 1997). Higher prevalence in adults may be owing to long time exposure to the vectors.…”
Section: Discussionmentioning
confidence: 95%
“…The degradation products (haeme monomers) formed are capable of generating toxic oxidants [18,89]. The occurrence of such a direct oxidative effect has been confirmed for Haemoproteus [18], the genus of malaria parasite present in the Seychelles warbler [44,45]. However, it is well possible that these parasite-generated oxidant concentrations are too low to be picked up by the ROMs assay.…”
Section: Discussionmentioning
confidence: 99%